The Effect of Massage Therapy on Preventing Delayed Onset Muscle Soreness (DOMS) in Sprinters - Lestari, Wiwit Azmi; Wardani, Ratna; Haryono, Haryono (Poltekkes Kemenkes Tanjung Karang, 2025)
Sports significantly contribute to students' physical and mental development, enhancing fitness and social skills. However, high-intensity training, such as sprinting, often results in Delayed Onset Muscle Soreness (DOMS), which can impair athletic performance and motivation. Massage manipulation therapy is a physiotherapeutic approach aimed at preventing and alleviating DOMS symptoms while increasing the Range of Motion (ROM) and reducing muscle pain in sprinter athletes at SMAN 91 Jakarta. This quasi-experimental study employed a pre-test and post-test design with three groups: ESK (effleurage, shaking, kneading, n=15), ESH (effleurage, shaking, hacking, n=16), and a control group (n=13). Interventions were administered once weekly over four weeks. ROM was measured using a goniometer, and muscle soreness was assessed via the Visual Analog Scale (VAS). Data were analyzed using the Kolmogorov-Smirnov and Shapiro-Wilk tests for normality, the Friedman test, and further analysis using the Kruskal-Wallis test for within-group differences. The ESK group showed a significant reduction in muscle soreness from a mean of 3.48 to 1.91 (p<0.005), while the ESH group exhibited a significant improvement in ROM from a mean of 1.56 to 3.06 (p<0.005). The control group showed no statistically significant changes in either variable. Massage manipulation therapy was effective in reducing muscle pain and enhancing ROM. ESH was more effective for improving ROM, whereas ESK was more effective for reducing pain. These findings emphasize the importance of combining multiple Massage techniques for comprehensive physiotherapy benefits in school-based athletic training.